Effects of traditional Chinese mind-body exercise-Baduanjin for type 2 diabetes on psychological well-being: A systematic review and meta-analysis - Lingjun Kong; Lingjun Kong; Jun Ren; Sitong Fang; Tianxiang He; Xin Zhou; Xin Zhou; Min Fang; Min Fang; Min Fang (Frontiers in Public Health, 2022)
BackgroundType 2 diabetes is considered one of the most psychologically demanding chronic conditions. Patients suffering from this disease often have poor psychological well-being due to emotional stress. Baduanjin exercises, a traditional Chinese mind-body exercise, are used in the management of type 2 diabetes, especially for mental health. However, the effect of Baduanjin exercises on psychological well-being of patients with type 2 diabetes maintains controversial. Therefore, this systematic review was conducted to evaluate the effects on psychological well-being of Baduanjin exercises for type 2 diabetes.MethodsSix electronic databases were searched from their inception to March 2022 for randomized controlled trials of Baduanjin exercises for type 2 diabetes. Two reviewers independently extracted data and assessed methodological quality based on PEDro scale. The subgroup analysis was conducted based on different control interventions. The Cochran Q statistic and I2 were applied to assess the heterogeneity.ResultsTwenty-seven studies between 2005 and 2019 were included in our review. Most of them exceeded the cutoff score 6 based on the PEDro scale. In psychological well-being, the aggregated results indicated that Baduanjin exercises showed positive effects in psychological well-being (SMD, 0.96; 95% CI, 0.57 to 1.36; p < 0.00001), depression (SMD, 1.03; 95% CI, 0.08 to 1.97; p = 0.03), anxiety (SMD, 0.88; 95% CI, 0.30 to 1.46; p = 0.003), and mental health (SMD, 0.72; 95% CI, 0.42 to 1.02; p < 0.00001). In glycemic control, Baduanjin exercises showed better improvements in FBG (SMD, 0.53; 95% CI, 0.34 to 0.72; p < 0.00001), HbA1c (SMD, 0.58; 95% CI, 0.41 to 0.75; p < 0.00001), and 2-hPBG (SMD, 0.56; 95% CI, 0.08 to 1.03; p = 0.02) compared with usual care/education. However, Baduanjin exercises only showed better improvements in HbA1c when compared with other exercises.ConclusionsThe traditional Chinese mind-body exercise-Baduanjin is a beneficial comprehensive therapy for type 2 diabetes, especially in promoting psychological well-being.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=110034.